On common agency with informed principals - Lima, Rafael Coutinho Costa (2008)
This thesis consists of three chapters that have as unifying subject the frame-work of common agency with informed principals. The first two chapters analyze the economic effects of privately informed lobbying applied to tariff protection (Chapter 1) and to customs unions agreements (Chapter 2). The third chapter investigates the choice of retailing strutures when principals (the producers) are privately informed about their production costs. Chapter 1 analyzes how lobbying affects economic policy when the interest groups have private information. I assume that the competitiveness of producers are lobbies private information in a Grossman and Helpman (1994) lobby game. This allows us to analyze the e¤ects of information transmission within their model. I show that the information transmission generates two informational asymmetry problems in the political game. One refers to the cost of signaling the lobby's competitiveness to the policy maker and the other to the cost of screening the rival lobby's competitiveness from the policy maker. As an important consequence information transmission may improve welfare through the reduction of harmful lobbying activity. Chapter 2 uses the framework of chapter 1 to study a customs union agreement when governments are subject to the pressure of special interest groups that have better information about the competitiveness of the industries they represent. I focus on the agreement's effect on the structure of political influence. When join a customs union, the structure of political pressure changes and with privately informed lobbies, a new effect emerges: the governments can use the information they learn from the lobby of one country to extract rents from the lobbies of the other country. I call this the 'information transmission effect'. This effect enhances the governments'bargaining power in a customs union and makes lobbies demand less protection. Thus, I find that information transmission increases the welfare of the agreement and decreases tari¤s towards non-members. I also investigate the incentives for the creation of a customs union and find that information transmission makes such agreement more likely to be politically sustainable. Chapter 3 investigates the choice of retailing structure when the manufacturers are privately informed about their production costs. Two retailing structures are analyzed, one where each manufacturer chooses her own retailer (exclusive dealing) and another where the manufacturers choose the same retailer (common agency). It is shown that common agency mitigates downstream competition but gives the retailer bargaining power to extract informational rents from the manufacturers, while in exclusive dealing there is no downstream coordination but also there are no incentives problem in the contract between manufacture and retailer. A pre- liminary characterization of the choice of the retailing structure for the case of substitute goods shows that when the uncertainty about the cost increases relatively to the size of the market, exclusive dealing tends to be the chosen retailing structure. On the other hand, when the market is big relatively to the costs, common agency emerges as the retailing structure. This thesis has greatly benefited from the contribution of Professors Humberto Moreira and Thierry Verdier. It also benefited from the stimulating environment of the Toulouse School of Economics, where part of this work was developed during the year of 2007.